Dominasi Politik dalam Pemerintahan Indonesia: Faktor Penyebab Dan Reformasi Partai Menuju Pemerintahan Demokratis Efektif - Hendrico Tampubolon (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
This article examines the importance of political and governance reform in Indonesia as a means to establish a government that is more transparent, efficient, and responsive to public interests. The dominant influence of politics in governmental policymaking constitutes one of the main challenges within Indonesia’s governance system. The dominance of major political parties in the political arena often results in policies driven primarily by short-term party interests rather than the public good. Consequently, reform of the political party system and the electoral system becomes a crucial step in improving the quality of democracy in Indonesia. This study also discusses how decentralization of power can enhance regional welfare by granting local governments greater authority to formulate policies that correspond to local needs and conditions. The electoral system is another central focus of this study, particularly the proposal to adopt a mixed-member proportional (MMP) system to create fairer and more balanced parliamentary representation, thereby reducing disparities in power distribution between large and small political parties. The main recommendations derived from this analysis include electoral system reform, strengthening the role of smaller political parties, and expanding decentralization to accelerate equitable development across Indonesia. The implementation of these reforms is expected to improve democratic quality, reinforce political stability, and realize a government that is more responsive to the interests of society.